Influência dos sistemas de gestão da qualidade no processo de projeto de empresas construtoras - Ricardo Estanislau Braga (2011)
In despite of the fact that there are several works in recent literature outlining the impact of Quality Management Systems in Brazilian construction companies, there are few studies focusing specifically on the influence of ISO9001 and Conformity Assessment System (SiAC) in the design process of these companies. In this context, this paperfocuses the specific requirements of these systems that impact on the design process, how construction companies are implementing these requirements and what its effective impact on design process management. An exploratory study was conducted in five buildingconstruction companies, and the results are reported and analyzed. As highlighted aspects it can be noted that the implementation of quality management systems has resulted in an enhancement of the design coordination process, improving the control over the design information flow, a better control of project documentation and an improvement inplanning the design process. Moreover, activities of review, verification and validation are not always properly carried out, although the introduction of quality management systems is representing a first step in that direction.